Effects of Cycloheximide on the Response of Intestinal Mucosa to Cholera Enterotoxin - Kimberg, Daniel V. (1973)
Prior studies have indicated that effects of cholera enterotoxin (CT) on the small intestine are delayed in onset and involve an interaction with adenyl cyclase in the mucosa. It has also been shown that the administration of cycloheximide to rabbits in doses which inhibit crypt cell mitoses (20 mg/kg), diminishes CT-induced fluid production in jejunal loops. These latter studies have been interpreted as indications that CT-related intestinal secretion is a crypt cell function and that it is mediated by a CT-induced protein. The present study was undertaken to delineate more precisely the nature of the interaction in the intestine between cycloheximide and cholera toxin. Pretreatment of rabbits with cycloheximide reduced by 60% the secretory response to CT in isolated ileal loops with intact blood supply. Sodium and chloride flux measurements on mucosa isolated from these and control loops indicated that this antisecretory effect of cycloheximide persists in vitro. Measurements of radioactive leucine incorporation into mucosal protein indicated that the dose of cycloheximide employed inhibited protein synthesis by 90%. This inhibitory effect was shown to be independent of any effect of cycloheximide on amino acid uptake across the brush border. Measurements of adenyl cyclase activity and cyclic AMP levels in ileal mucosa of cycloheximide pretreated and control animals indicated that cycloheximide did not diminish the CT-induced increases in these parameters. These observations demonstrate that cycloheximide reduces CT-induced intestinal fluid production without interfering with the CT-induced augmentation of adenyl cyclase activity or the consequent rise in cyclic. AMP concentration. Since the antisecretory effect of cycloheximide persists in vitro, it probably involves a direct interaction of the antibiotic with mucosal cell ion transport mechanisms rather than an indirect effect mediated by other humoral or neurogenic factors. The present observations also suggest that the secretory response of the intestine to CT involves neither the synthesis of new adenyl cyclase nor that of a protein modifying its activity.